RELATIONSHIPS BETWEEN KNOWLEDGE SHARING AND REWARD SYSTEMS IN ORGANIZATIONS: THE CASE OF ERENCO - Muammer Mesci; Süleyman Ağraş; Yalçın Karagöz (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Knowledge is the most critical factor of sustainable competitive advantage in today’s knowledge based economy and competitive conditions. In different structure from traditional resources investment on Knowledge and using it requires a deal number of activities holistically. These investments and activities may be from internal or external perspectives. To invest on knowledge from the points of internal perspective, it is clear that providing knowledge sharing is critical. At this point, reward systems have an important function in sharing knowledge with co-workers and organization itself. In this study, it is aimed to investigate the roles and impacts of reward systems in upgrading knowledge sharing. In the scope of the aim, a case study analyze has been designed and ERDEMIR Engineering Management and Consulting Services Inc has been determined as the analyze unit. In the study, survey technique is used for collecting research data. Obtained data has been analyzed by using descriptive analyze techniques by means of SPSS 16.00 program. The findings of the research have demonstrated that reward systems have increased the knowledge sharing in the organization. Descriptive statistics have proved that demographics of participants effect in the relationships between knowledge sharing and reward systems.